تبني الأعمال الإلكترونية ودوره في تحسين جودة الخدمات - كريبط ،سارة; حديد، نوفيل (جامعة الوادي University of Eloued, 2025)
في ظل التطور السريع لتكنولوجيا المعلومات، أصبح من الضروري إعادة تنظيم النماذج التشغيلية والإدارية لتلبية متطلبات العصر الرقمي. تبحث الدراسة في تأثير تبني الأعمال الإلكترونية على تحسين جودة الخدمات، مع تسليط الضوء على حالة شركة المياه والتطهير "سيال" في الجزائر. فقد أسهمت الرقمنة واعتماد الحلول التكنولوجية الحديثة، مثل نظم المعلومات الجغرافية وأنظمة إدارة العلاقة مع العملاء ومنصات الدفع الإلكتروني، في تحديث البنية التحتية وتحسين الكفاءة التشغيلية، مما أدى إلى تقديم خدمات أكثر دقة وسرعة وشفافية. كما تناولت الدراسة مفهوم الأعمال الإلكترونية والعوامل الدافعة لاعتمادها، محللةً أبعاد جودة الخدمة والتحديات التقنية والتنظيمية والأمنية المرتبطة بعملية التحول الرقمي. وتخلص إلى أن تبني الأعمال الإلكترونية يُعد استراتيجية شاملة تعزز التميز وتضمن استدامة النمو والتطور في ظل بيئة دائمة التغير In light of the rapid development of information technology, it has become necessary to reorganize operational and administrative models to meet the demands of the digital age. This study examines the impact of adopting e-business on improving service quality, with a focus on the case of Algeria's water and sanitation company "SEAAL". Digitalization and the adoption of modern technological solutions, such as Geographic Information Systems, Customer Relationship Management Systems, and Electronic Payment Platforms, have contributed to modernizing the infrastructure and enhancing operational efficiency, resulting in more precise, faster, and more transparent services and increased customer satisfaction. The study also addresses the concept of ebusiness and the driving factors behind its adoption, analyzing the dimensions of service quality and the technical, organizational, and security challenges associated with digital transformation. It concludes that adopting e-business is a comprehensive strategy that enhances excellence and ensures sustainable growth and development in an ever-changing environment.
Adoption of e-business and its role in improving the quality of services: A case study of the Algerian Water and Sanitation Company "SEAAL"
مقال
Keywords: الأعمال الإلكترونية; جودة الخدمة; التحول الرقمي; تكنولوجيا المعلومات; شركة سيال; Service Quality; Digital Transformation; SOCIAL SCIENCES::Statistics, computer and systems science::Informatics, computer and systems science::Information technology